Prediction of the Quality of Life of Menopausal Women Based on Health Literacy and Self-Efficacy - Sara Jafarigiv; Nooshin Peyman; Habibollah Esmaily; Mohammad Tajfard (Journal of Education and Community Health)
Aims: Menopause is one of the most critical periods in women's lives that although it is a physiological event, but it is accompanied by complications that affect women's quality of life. The aim of this study was to determine the prediction of the quality of life of menopausal women based on health literacy and self-efficacy. Instrument & Methods: This cross-sectional descriptive-analytical study was conducted on 400 postmenopausal women referred to comprehensive health centers in Mashhad in 2018 who were selected by random cluster sampling method. The research tool was a 4-part questionnaire including demographic characteristics, test of functional health literacy in adults (TOFLA), Sherer general self-efficacy and quality of life in menopause. Data were analyzed by SPSS 22 software using Kruskal-Wallis, Mann-Whitney, Spearman’s correlation, and linear regression model. Findings: There was a significant correlation between health literacy (r=-0.352) and self-efficacy (r=-0.338) with quality of life (p<0.001). Self-efficacy, health literacy, marriage age, type of delivery, vitamin D consumption, dairy consumption, and fruit were predictors of quality of life in menopausal women (p<0.05). Self-efficacy and health literacy predicted 18% and the other variables predicted 31% of variance in quality of life. Conclusion: Health literacy and self-efficacy are two factors affecting the quality of life of postmenopausal women.